2022
DOI: 10.1101/2022.12.16.520768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct neural perturbations reveal a dynamical mechanism for robust computation

Abstract: The rich repertoire of skilled mammalian behavior is the product of neural circuits that generate robust and flexible patterns of activity distributed across populations of neurons. Decades of associative studies have linked many behaviors to specific patterns of population activity, but association alone cannot reveal the dynamical mechanisms that shape those patterns. Are local neural circuits high- dimensional dynamical reservoirs able to generate arbitrary superpositions of patterns with appropriate excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 111 publications
(170 reference statements)
0
16
0
Order By: Relevance
“…Second, in contrast with many passive electrodes, it is not currently possible to use the Neuropixels probe to deliver intracortical microstimulation (ICMS), though future versions of the probe may add this functionality. The Neuropixels technology is, however, capable of recording while stimulating through external electrodes, as recently demonstrated by O’Shea, Duncker, et al 13 . Third, the Neuropixels 1.0-NHP design is not explicitly optimized for chronic implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, in contrast with many passive electrodes, it is not currently possible to use the Neuropixels probe to deliver intracortical microstimulation (ICMS), though future versions of the probe may add this functionality. The Neuropixels technology is, however, capable of recording while stimulating through external electrodes, as recently demonstrated by O’Shea, Duncker, et al 13 . Third, the Neuropixels 1.0-NHP design is not explicitly optimized for chronic implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The capabilities provided by these approaches have led to important new discoveries, such as a continuous attractor network of grid cells in the rat hippocampus 9 , establishing a causal topographical mapping between activity in the cortex and striatum in mice 4 , and revealing how thirst modulates brain-wide neural population dynamics in mice 7 . The Neuropixels 1.0 probe has also been used to record neurons acutely in nonhuman primates (NHPs) like macaques [10][11][12][13] and in humans 14,15 , but their short length (10 mm) restricts access to all but the most superficial targets, and the thinness of the shanks (24 µm) renders them fragile and difficult to insert through primate dura mater.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this role in inputs selection, our analysis revealed that non-normal dynamics might additionally result in the transient amplification of relevant inputs in PFC. Non-normal transient amplification had previously been proposed to play a role in the processing of external inputs [21][22][23] , as well as computations as varied as maintaining inputs in working-memory 24 , generating the transient neural activations required for generating movements 25 and mediating robustness to perturbations 26 . Our observation of two distinct stages in PFC dynamics during decision formation is evocative of a recently proposed mechanisms relying on transient amplification to optimally load information onto an attractor 22 .…”
Section: Discussionmentioning
confidence: 99%
“…While here we fitted activity from only a relatively short time window from each trial (the 750ms of random dots presentation), recent findings suggests that linear models may not be outperformed by non-linear models in capturing cortical dynamics even over longer time-windows 45 . Nonetheless, analyses based on non-linear models are becoming increasingly common, given their flexibility in capturing very complex neural data 35 and the interest in modeling biological constraints that cannot be captured by linear models 46 (but see 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation